2021
DOI: 10.1016/j.ophtha.2020.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SARS-CoV-2 in Tears of Patients with Moderate to Severe COVID-19

Abstract: Purpose To investigate the presence of SARS-CoV-2 RNA in tears of patients with moderate to severe coronavirus disease 2019 (COVID-19). Design Cross-sectional study. Participants Patients with laboratory-proven moderate to severe COVID-19. Methods Tears were collected within 48 hours of laboratory confirmation using 3 methods: conjunctival swab plus Schirmer’s test strips (group 1), conjunctival swab (group 2), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 27 publications
6
109
3
3
Order By: Relevance
“…Subsequent studies confirmed that coronavirus infection is rarely associated with conjunctivitis, with occasional cases reported in patients with established COVID-19 infection, along with isolated cases of conjunctivitis as a presenting sign. 19 20 On the contrary, Arora et al 21 reported the presence of viral RNA in tears of one-fourth of patients with moderate to severe COVID-19 without conjunctivitis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies confirmed that coronavirus infection is rarely associated with conjunctivitis, with occasional cases reported in patients with established COVID-19 infection, along with isolated cases of conjunctivitis as a presenting sign. 19 20 On the contrary, Arora et al 21 reported the presence of viral RNA in tears of one-fourth of patients with moderate to severe COVID-19 without conjunctivitis.…”
Section: Discussionmentioning
confidence: 99%
“…The ocular mucosa and the nasopharynx are connected by the nasolacrimal duct. When splashes reach the cornea or conjunctiva, they can penetrate the nasolacrimal duct and be transported to the nasopharynx and trachea [ 44 , 45 ]. Ocular manifestations seem frequent, and high-frequency hand–eye contact correlates with conjunctival congestion [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…When liquid splashes occur at eye, it can be partially absorbed by the cornea and conjunctiva but also get into the nasal cavity through the nasolacrimal duct, be transported toward the nasopharynx and trachea, and at this point swallowed into the gastrointestinal tract. So logically viruses contained in the liquid splashes to which the eye is exposed can be transported to the nasopharynx and respiratory tract mucosa [34,35]. Ocular manifestations seem frequent, and high-frequency hand-eye contact was correlated with conjunctival congestion [36,37].…”
Section: Discussionmentioning
confidence: 99%